System Based Ship Design for Fast Ferry - Ericza Damaranda Sugita; Wasis Dwi Aryawan; Rizka Arie Hutama (Institut Teknologi Sepuluh Nopember, 2020)
Design is a complex process where creativity and analytical skills are needed for success. At present, the development of design methods has moved towards field practice rather than theory. The main objective of this research is to determine the design of fast ferry to transport passengers from Sorong to other coastal areas in West Papua. The method used in this fast ferry design is the System Based Ship Design (SBSD) method which uses a strategy to reduce the number of loops to find the best concept by giving greater emphasis to the analysis of functions. The design study begins with a mission statement and establishes the main function requirements. Then find the area and volume needed on each deck that is determined by using life size experiment and model test experiment to determine the initial main dimensions. Then, alternatives to be evaluated against the relevant framework conditions. The results of this study is catamaran fast ferry design with a load capacity of 100 passengers and has a speed of 40 knots. It has main dimensions of length of 40,387 m, breadth of 11.02 meters, and draft of 1.5 meters. It is propelled by water jet propulsion and aluminium material applied.